STARS AKBUZAT AND KUKBUZAT IN ASTROMYTHOLOGY OF TURKIC PEOPLES OF CENTRAL ASIA (Scientific journal of the Fergana State University, 2023)
This article analyzes the ancient astromythological ideas and cosmogonic myths recorded in the folklore of the Turkic peoples of Central Asia. Based on a comparative analysis, it is proved that the genetic origins of Uzbek astral myths are directly related to ancient Turkic mythology.